PENGARUH MODELPROBLEM BASED LEARNING DAN COOPERATIVE LEARNING TIPE THINK PAIR SHARE TERHADAP PRESTASI BELAJAR IPA DITINJAU DARI MINAT SISWA KELAS V SD KECAMATAN BULUKERTO TAHUN PELAJARAN 2012/2013 - RIKA YUNI AMBARSARI (JURNAL MITRA SWARA GANESHA, 2014)
The purpose of this study was to investigate: (1) Whether use of model Problem Based Learning, and Think Pair Share method have positive correlation towards the students' learning outcomes of of Natural Sciences, (2) whether students' different levels of interest (high, medium, and low interest) affects the learning outcomes , (3) whether there is a positive corelation between Problem Based Learning and Think Pair Share, students' interest, and of the learning outcomes of Natural Science.The method used in this research was experimental research. The populations in this study were all elementary school students in Bulukerto District, Wonogiri Regency, whereas the sub-populations were the fifth grade students in Bulukerto District Elementary School academic year 2012/2013. The sample of the research was collected by using multistage cluster random sampling. Questionnaires were used to investigate the students' interest, while test was used to measure students' learning outcomes . The data was analyzed by using two-way analysis method..Based on those results, it can be concluded that: (1) There is a positive effect of using the models Problem Based Learning and Coperative type Think Pair Share the Natural Sciences towards the students' learning outcomes (F count> F table or 15,48> 4.07), (2) Students' different levels of interest (low, medium, and high interest) affect the learning outcomes of Natural Science (F count > F table or 17,7281>3,21), (3) There is not positive correlation between Problem Based Learning and Cooperative learning types Think Pair Share, students' interest, and students' learning outcomes of Natural Sciences (F count > F table or 2,36<3,21).Based on the study, it is expected that teachers will able to implement the most suitable method in the learning process. . Teachers should work hard to increase students' interest, because the learning method and student interest will affect the learning outcomes.